Globalization and the rise and fall of cognitive control - Mohsen Mosleh (Nature Portfolio, 2020)
Humankind is in a period of unprecedented cognitive sophistication as well as globalization. Here, using an evolutionary game theory model, the authors reveal ways in which the transition from local to global interaction can have both positive and potentially negative consequences for the prevalence of cognitive sophistication in the population.